Occurrence of T-2 toxin in processed cereals and pulses in Turkey determined by HPLC and TLC - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2001)
The purpose of this study was to investigate the T-2 toxin level of contaminated cereal and pulse products in Turkey. T-2 toxin was detected using high performance liquid chromatography (HPLC) with UV detection at 208 nm and thin layer chromatography (TLC) was used for confirmation of the T-2 toxin-contaminated samples (greater than or equal to1 ppm). The recovery was 93 +/-3.3% (SD 3.29, n = 5) for chickpea spiked with a known amount of T-2 toxin (1 ppm). The detection limits for T-2 toxin for HPLC and TLC were 25 ng per injection and 50 ng per spot, respectively. A total of 50 commercially available cereal and pulse product samples, collected from markets and street bazaars, were analysed. Incidences of T-2 toxin detected in cereal and pulse products were 23.5% and 31.2%, respectively and the maximum detected amount was 1.9 ppm in a sample of dried beans. The incidence of toxin-contaminated specimens is not so low relative to the volume of specimens produced.
Keywords: T-2 toxin; cereals and pulses; HPLC; TLC; PERFORMANCE LIQUID-CHROMATOGRAPHY; TRICHOTHECENE MYCOTOXINS; RETENTION INDEXES; SCREENING METHOD; HT-2 TOXIN; FUSARIUM; GRAINS; CORN; PHARMACOKINETICS; METABOLITES